Direct preparation of solid carbon dots by pyrolysis of collagen waste and their applications in fluorescent sensing and imaging - Qin, Xiaoyun; Fu, Cuicui; Zhang, Jin; Shao, Wenlong; Qin, Xiaomei; Gui, Yanghai; Wang, Lan; Guo, Huishi; Chen, Fenghua; Jiang, Liying; Wu, Gang; Bikker, Floris J.; et al. (Frontiers in Chemistry, 2022)
The fluorescent carbon dots (CDs) have found their extensive applications in sensing, bioimaging, and photoelectronic devices. In general terms, the synthesis of CDs is straight-forward, though their subsequent purification can be laborious. Therefore, there is a need for easier ways to generate solid CDs with a high conversion yield. Herein, we used collagen waste as a carbon source in producing solid CDs through a calcination procedure without additional chemical decomposition treatment of the raw material. Considering a mass of acid has destroyed the original protein macromolecules into the assembled structure with amino acids and peptide chains in the commercial extraction procedure of collagen product. The residual tissues were assembled with weak intermolecular interactions, which would easily undergo dehydration, polymerization, and carbonization during the heat treatment to produce solid CDs directly. The calcination parameters were surveyed to give the highest conversion yield at 78%, which occurred at 300°C for 2 h. N and S atomic doping CDs (N-CDs and S-CDs) were synthesized at a similar process except for immersion of the collagen waste in sulfuric acid or nitric acid in advance. Further experiments suggested the prepared CDs can serve as an excellent sensor platform for Fe3+ in an acid medium with high anti-interference. The cytotoxicity assays confirmed the biosafety and biocompatibility of the CDs, suggesting potential applications in bioimaging. This work provides a new avenue for preparing solid CDs with high conversion yield.